Sperm donation perinatal outcomes in an Australian population cohort. Issue 12 (17th August 2017) - Adams, Damian; Fernandez, Renae; Moore, Vivienne; Willson, Kristyn; Rumbold, Alice; de Lacey, Sheryl; Scheil, Wendy; Davies, Michael
Abstract: Aim: To compare perinatal outcomes for neonates conceived with donated sperm with those for neonates conceived spontaneously in an Australian population cohort. Methods: Perinatal outcomes for all births in South Australia for the period January 1986–December 2002 were linked with assisted reproductive treatment records to determine those conceived from donated sperm. Birth outcome measures were analyzed using Student's t ‐test and logistic regression using generalized estimating equations to determine statistical significance. Results: Donor sperm neonates were not significantly different from their spontaneously conceived counterparts in terms of mean birthweight, low birthweight, preterm delivery, small for gestational age, or large for gestational age. They were, however, significantly more likely to be born at lower mean gestational age ( P = 0.012), and to have preterm delivery with low birthweight ( P = 0.008), when controlling for maternal age, parity, ethnicity, socioeconomic quartile and baby's sex. These associations were not apparent when singletons and twins were considered separately. Conclusion: There was some evidence of compromised perinatal outcomes for donor sperm neonates compared with their spontaneously conceived counterparts, which appeared to be partly attributable to multiplicity.